2019
DOI: 10.3390/cryst9070356
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Partially Dehydrogenated ε-FeOOH

Abstract: Hydrogen in hydrous minerals becomes highly mobile as it approaches the geotherm of the lower mantle. Its diffusion and transportation behaviors under high pressure are important in order to understand the crystallographic properties of hydrous minerals. However, they are difficult to characterize due to the limit of weak X-ray signals from hydrogen. In this study, we measured the volume changes of hydrous ε-FeOOH under quasi-hydrostatic and non-hydrostatic conditions. Its equation of states was set as the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…This is previously regarded as a symbol of anisotropy of the charge carrier transportation in the crystallites 40 . While both our x-ray diffraction experiment and literature data indicate that ε-FeOOH is a stable phase throughout the pressure range we have investigated 27,41,42 , the appearance of the second arc coincides with the spin-paring of Fe 42 . The spin transition of Fe may create grain boundaries between the high-spin and low-spin domains.…”
Section: Resultssupporting
confidence: 53%
“…This is previously regarded as a symbol of anisotropy of the charge carrier transportation in the crystallites 40 . While both our x-ray diffraction experiment and literature data indicate that ε-FeOOH is a stable phase throughout the pressure range we have investigated 27,41,42 , the appearance of the second arc coincides with the spin-paring of Fe 42 . The spin transition of Fe may create grain boundaries between the high-spin and low-spin domains.…”
Section: Resultssupporting
confidence: 53%
“…DOI: https://doi.org/10.2138/am-2021-7541. http://www.minsocam.org/ slowly increases with increasing FeOOH content (Gleason et al, 2013;Hsieh et al, 2020;Ohira et al, 2019;Thompson et al, 2020;Zhuang et al, 2019). It has been proposed that ferropericlase (Mg,Fe)O and ferromagnesite (Mg,Fe)CO would uptake more iron when entering the low spin state in the lower mantle (Cerantola et al, 2017;Lobanov et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the spin transition pressure of the Delta52 phase is between 41 and 45 GPa via the laser Raman experiment using neon as a pressure-transmitting medium in this study. The spin crossover of Delta52 is 3-5 GPa lower than that of ε-FeOOH by XRD experiments using the same pressure-transmitting medium (Thompson et al, 2020;Zhuang et al, 2019). It should be mentioned that Gleason et al (2013) reported that the spin crossover of ε-FeOOH is much wider…”
Section: The Effect Of Feooh Content On the Spin Transition Of δ-(Almentioning
confidence: 93%
See 1 more Smart Citation